Evaluation of antiproliferative and antimetastatic effects of heparin and erythropoietin on B16f10 melanoma cell line - Koçak, F. E.; Erdoğan, E.; Ozyıgıt, F.; Yerlıkaya, A. (Cellular and Molecular Biology, 2013)
A number of chemotherapeutic agents and treatment strategies have been developed or designed to treat cancer patients. However, chemotherapeutic regimens frequently cause side-effects, one of which is anemia, a severe clinical problem for cancer patients. Erythropoietin is commonly used to treat anemia and reduce blood transfusions in cancer patients. Another agent which has potential use in cancer therapy is heparin, a glycosaminoglycan with a negative charge, known to increase the clearance of tumor cells from the blood in mice and also has anti-metastatic effects. In this current study, we investigated the effects of rEpo and heparin either as single agents or in combination on B16F10 melanoma cells. Contrary to our expectations based on the previous in vitro and in vivo studies, we have not found a significant growth-promoting effect of rEpo on B16F10 cells. We have also not observed a significant cytotoxic effect of heparin on B16F10 melanoma cell as assayed by MTT test (p > 0.05). However, heparin did significantly prevent the migration/proliferation of B16F10 cell in the wound assay as compared to the control cells after 24 h of incubation (p < 0.001). In addition, this effect of heparin was not prevented when rEpo was present in the medium in the wound assay (p < 0.01 as compared to the control). These results suggest that heparin may have a therapeutic potential as an anti-metastatic drug for cancer.